Análise do quadriênio (2017-2020) do Programa de Pós-graduação em Ciência da Informação da Universidade Federal do Ceará (PPGI-UFC) - Lopes, Sandra Vieira (2021)
The present work entitled: Analysis of the four-year period (2017-2020) of the Graduate Program in Information Science at the Federal University of Ceará (PPGI-UFC) presents the contribution and relevance of scientific productions made by the PPGCI-UFC with respect to the 1st assessment of CAPES (2017-2020) provided to the academic environment and to the society in which it is inserted. Thus, this study is guided by the objective: to analyze the scientific production of the faculty of the PPGCI-UFC in its first four years of existence (2017-2020). In order to achieve the general objective, the following specific objectives were created: 1- To survey the bibliographic production of the faculty members in the four-year period (2017-2020); 2- To create scientific production indicators based on the number of productions per document, and; 3- To know the Qualis Capes classification of the strata of the articles published in periodicals. This is a biographical and documental research of exploratory, quanti-qualitative nature that resulted in a diagnosis of the quadrennium from the collection of bibliographic data collected on the Sucupira platform. After data collection, they were organized in Microsoft Excel® software, in which tables and graphs were prepared for viewing the results. After the interpretation of the analyses it was found that the first two years were favorable to the research, however, the third year (2019) showed a considerable decrease in numerical terms of scientific production. However, the last year presented in the data analysis shows how the production was stimulated and resulted in a positive and significant growth.